(untitled) (Dhaka Shishu (Children) Hospital Journal, 2021)
Background: Prematurity is the largest cause of neonatal mortality. They need incubators or radiant warmers which are expensive and very difficult to arrange in a resource constraint country. Kangaroo mother care (KMC) had been proposed as an alternative to conventional neonatal care for low birthweight (LBW) babies. Objectives: To observe the benefits of Kangaroo mother care in preterm low birth weight babies. Methods: This randomized controlled trial was conducted over 6 months in Dhaka Shishu Hospital. Neonates who were <1800 gm and hemodynamically stable were enrolled. Total 80 neonates were enrolled and divided into 2 groups: Kangaroo mother care group and conventional method care group (incubator/warmer). The mother or caregiver were taught for KMC, supervised by trained nurses round the clock. KMC was given at least 2 hours at a time and at least 12 hours in a day. When the baby was not in KMC at that time the baby was placed in cot with adequate coverings. During hospital stay both the groups were monitored. Results: In KMC group 25% and conventional care group 40% neonates became hypothermic. Among the study population 35% neonates in KMC and 65% neonates in conventional care groups developed sepsis (p= 0.007). More KMC babies were exclusively breastfed at the end of the study (95% vs 60%). The KMC babies had shown better growth: weight gain per day (18.35±7.81 grams vs 13.55±4.89 p<0.001) and length (0.99±0.70 vs 0.71±0.44 cm, p = 0.03). KMC babies were discharged earlier than conventional care baby. Conclusion: KMC provides significant improvement in exclusive breast feeding, reduction of infection, decrease hospital stay and gaining weight of the babies. It also helps in maintaining temperature better than conventional care. DS (Child) H J 2020; 36(2): 107-113